Comets and How to Observe Them - Schmude, Richard; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Comets have inspired wonder, excitement and even fear ever since they were first observed. They contain material from early in the life of the Solar System, held in deep-freeze. This makes them key in our understanding of the formation and evolution of many Solar System bodies. Recent ground- and space-based observations have changed much in our understanding of comets. Comets and How to Observe Them gives a summary of our current knowledge and describes how amateur astronomers can contribute to the body of scientific knowledge of comets. This book contains many practical examples of how to construct comet light-curves, measure how fast a comet$1 (Bs coma expands, and determine the rotation period of the nucleus. All these examples are illustrated with drawings and photographs.s
Comets: An Overview -- Comets 9P/Tempel 1, 1P/Halley, 19P /Borrelly, and 81P/Wild 2 -- Observing Comets with the Unaided Eye and Binoculars -- Observing with Small Telescopes -- Observing with Large Telescopes.
Keywords: Physics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy